Psychocorreksion of prevention and elimination of mental health problems of school-age children - Djalalova Mohinur Abdusator's Qizi (Euro Asian Journal Publishing, 2024)
The article outlines the results and analysis of a correctional program to prevent and address mental health problems for preschool youth children. The article also cited work on aggressive cases of children's mental health criteria.
Keywords: research; child; program; mental health